The method of dual integral equations for analysis of heat transfer processes - Mandrik, P. A. (Mathematical Modelling and Analysis, 2001)
The paper is devoted to the study of a heat conduction equations with mixed boundary conditions on a surface of a researched solid. The method based on the Laplace and Hankel transforms is suggested for the first time to reduce such differential problems to dual integral equations and to obtain the solution in the close form. Method allows to determine analytically regularities of time‐space development of appropriate temperature fields. Dualiųjų integralinių lygčių metodas šilumos pernešimo procesų analizėje Santrauka. Straipsnyje nagrinėjamos šilumos pernešimo lygtys su mišriomis kraštinėmis sąlygomis tiriamo kūno paviršiuje. Metodas remiasi Laplaso ir Hankelio trasformacijomis, kurios suveda šį diferencialinį uždavinį į dualiąsias integralines lygtis. Metodas leidžia analitiškai apibrėžti įvairių temperatūrinių laukų laikinį – erdvinį kitimą. First Published online: 14 Oct 2010